Black ops the rise of special forces in the C.I.A, the S.A.S, and Mossad - Geraghty, Tony (Pegasus Books, 2012)
After ten challenging years in Afghanistan, the new U.S. strategy, aimed at winning hearts and minds rather than search-and-destroy, refocuses the conflict on Special Forces: unorthodox soldiers who work outside of traditional military forces to combine secret military operations with nation building. This book unveils the extraordinary evolution of this refined style of war-making from its roots in anti-guerrilla warfare in Ireland and Palestine, by way of the creation of the C.I.A., the S.A.S., the Green Berets, the American Office of Strategic Services (O.S.S.), and many others, including Mossad.